Filipino Cultural Values and Social Entrepreneurship Intention Among Gen Z Learners - Eric S Parilla; Richard Mariano; Venus Empuerto (Journal of Social Entrepreneurship Theory and Practice, 2026)
The study basically checked for the association between Cultural values of the Filipino and Social Entrepreneurship Intention among Generation Z learners, such as bayanihan and pakikipagkapwa–tao, with prosocial motivation acting as an intervening variable. The Quantitative Correlational study has imparted primary data collected by 910 Filipino Gen Z learners across Luzon, Visayas, and Mindanao using a Structured Survey and non-probability purposive sampling methods. Data was analyzed using Jamovi on descriptive statistics, regression analysis, and mediation analysis. Results indicate that the Formulation of cultural orientation and prosocial motivation was high, but possibly corresponding to social entrepreneurship intention. Both bayanihan and pakikipagkapwa–tao together significantly predict social entrepreneurship intention, according to the regression results, with the two ideologies collectively explaining 51.9% of its variance. According to the mediation analysis results, prosocial motivation significantly mediates the relationship between cultural indicators and entrepreneurial intentions, thereby underscoring its role in linking the two. The study adds to the body of knowledge by establishing a link between Filipino indigenous values and psychological mechanisms for discussing reasons to guide the youth in socially responsible enterprises. It therefore suggests that culture-rooted prosocial orientations are likely to outweigh other drivers of intention to engage in social entrepreneurship among Gen Z learners.